On the Trail of a Photo – A Tableau of the Serbian Orthodox Theological-Teaching School Graduates in Prizren in 1896 - Novakov, Aleksandra Ž. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This story of the life paths of the teachers and students of the seminary is told on the trail of a photograph, that is, a tableau of the graduates of the Serbian Orthodox Theological-Teaching School in Prizren, in 1896. It is about their contribution to education, church, Christianity, theology, literature, ethnology, and science. Like other photographs created in studios throughout the Serbian cultural space, they are more than documents, they are an inexhaustible treasure for historians and other cultural workers. They visually remind us of our ancestors and tell us about a time that no longer exists, the time of nobility. Professors and graduates are dressed according to the European style of clothing, unusual for those occasions and that time, when professors had to wear a fez, so as not to be distinguished from citizens of other religions. The place and time of the photograph is the 19th century, the Ottoman Empire, Kosovo Vilayet, the ‘Dark Vilayet’! An authentic 1896 photo from Prizren is a true rarity. There is no information on taking photos in the archival material of the Theological School, but one thing is certain, the photography was created in Prizren that year, but the name of the photographer is unknown. There are 27 people on the tableau, rector Ilarion (Ivan) Vesić, eight teachers, Trivun Dimitrijević, Kosta Lozanić, Mihailo S. Tasić, Milan Gajić, Sava Jakić, Danilo (Nedeljković), Vasilije Stojanović, Apostol Filipovic, and 18 graduates, Toma Burković, Ljubomir A. Bulatović Ibrijski, Milutin V. Vukić, Janićije (Naća) Živković, Janko Đorđević, Haralampije Ilić, Pantelija Mandić, Dusan Nekic, Milan Nikšić, Radivoje R. Orlović, Atanasije Petrović, Blagoje Petrović, Obrad Popović, Nikola Rožić, Mladen Stojanović, Petar Ćićarić, Vladimir Popović and Zdravko Tasić. This is the first generation of high school graduates who completed the six-year Serbian Orthodox Theological-Teaching School. The Council of the Theological School declared them capable of being teachers and they were issued with certificates of teacher training. When they finished their education, they were between 17 and 26 years old. Except for one student who continued his education at the Belgrade Theological School, all the others were appointed as teachers. Obviously, the need for trained teachers throughout Old Serbia was great that year. In further service, five students were ordained as priests, one teacher became a merchant. Only one former student finished the Spiritual Academy, and two continued their education after the Theological School. Of the 18 students, five were from Prizren, three from the surrounding area. For the first time, a student from Bosnia attended the Theological School. Four young men were from Macedonia, two from Montenegro, two from the Kingdom of Serbia, and one from Kosovo. Of the nine teachers, four had university degrees, two were monks, which was a requirement for the Theological School. In different years, they were able to make contact with the students and help them not only as teachers, but also as guardians, because it was a boarding school. The goal of the Theological School in Prizren was to educate and form an educated staff of teachers and priests, which it successfully realized. Teachers and priests in Old Serbia were, in addition to their vocation, a kind of national workers and cultural activists because the Theological School moulded them as patriots.
Keywords: theological school; Prizren; graduates; photo; tableau; teacher; priest